W7-X plasma diagnostics for impurity transport studies - Kubkowska, M.; Buttenschön, B.; Langenberg, A.; W7-X team (Вопросы атомной науки и техники, 2018)
The Wendelstein 7-X (W7-X) stellarator which is located in Greifswald, Germany is an experimental device for demonstration of steady-state plasma operation. It was commissioned at the end of 2015 and at the beginning, it was operated in the limiter configuration (5 poloidal uncooled graphite limiters) while starting from 2017 it has been equipped with a carbon uncooled divertor. With the launch of the device, new diagnostics have also been commissioned and tested. Understanding of impurity transport in stellarators is a crucial task in the optimisation process. At W7-X there are several spectroscopic systems which deliver information about plasma impurities. One of them is a pulse height analysis system (PHA) which collects soft X-ray spectra in the energy range from about 300 eV up to 20 keV with 100 ms temporal resolution. There are also X-ray imaging spectrometers XICS and HR-XIS which are devoted for measurements of spatio-temporal impurity emissivity of highly ionized ions with high temporal resolution (5 ms). Spectra in the VUV region are measured by the High-Efficiency XUV Overview Spectrometer (HEXOS).